Minimally Invasive Temporomandibular Joint Surgery Methods using Surgical Treatment of Hyaluronic Acid in Patients with Various Diseases - Chikobava, Sofi; Nikolaishvili, Marine; Gogiberidze, Mamuka (European Scientific Journal, ESJ, 2019)
The complex approach to the treatment of patients with RD has been elaborated at the department. At the preparatory stage, the doctor rheumatologist assesses the activity of the disease and, in case of necessity, provides the adjustment of therapy in order to get the lowest activity / remission of the main disease for about ≥1 months. Temporomandibular joint (TMJ) involvement occurs in patients with different rheumatic diseases (RDs). Pain, limitation of mouth opening can lead to significant problems. Conservative treatments for TMJ lesions are not always effective. Objective: to evaluate the efficiency of minimally invasive surgical interventions (TMJ arthrocentesis and arthroscopy) in patients with RDs. Patients and methods: In case of TMJ dysfunction (the mouth opening, closure, chewing, speaking), and lateral and/or protrusion, discomfort, pain, all the degenerative changes detected on MRI need surgical treatment. 80 patients turned to our clinic center. Most of them (n = 70) were diagnosed with RD. Objective examination resulted revealed 93.8% of cases of the limitation in mouth opening and the articulation disorder. 19 patients (28.1%) had masticatory muscle hypertonicity, mostly bilateral (88,9%). In 62.9% of patients participating in the study, the damage to TMJ according to the international classification of Wilkes was attributed to stage IV, in 21.9 and 14.9% - to stage III and V, respectively. The clinical and instrumental investigations, patients with stages IV and V according to the Wilkes International Classification, underwent TMJ arthroscopy and patients with III – TMJ arthrocentesis with arthro lavage. All the patients underwent TMJ magnetic resonance imaging at baseline and 6 months after treatment. After a surgical intervention, a gel containing hyaluronic acid was used as a fluid implant. 14th day and, 1, 6,12 months after the operation, the examination of the disks in the joints showed their normal movement and normal amplitude of the condyles. Results and discussion: After surgical treatment, all the groups were noted to have a significant decrease in TMJ pain intensity compared with the baseline level; moreover, the severity of TMJ pain most significantly decreased on day 7 after surgery. Later on, positive changes remained 12 hours after the operation, the patient noted mild periodic pain of the right TMJ while the mouth opening, which was estimated by VAS scale up to 10 mm by the patient. The size of the mouth opening increased up to 35 mm.